От социологии к оценке - Фролова, Ольга (Studia Rossica Posnaniensia, 2019)
The article deals with figurative meanings of nominations of the social hierarchy relating to the upper, middle and lower strata of Russian society of the 18th and 19th centuries, and their reflection in the explanatory dictionary of the beginning of the 21st century. The use of adjectives, formed from personal nouns in the Russian National Corpus in the period 2000–2017, is analyzed.